Methodology for the selection of materials according to LCA guidelines applied to the design of temporary housing in tropical climates (REVISTA NODO, 2014)
In order to mitigate the impact caused by the loss of home due to constant natural events, the design of a suitable construction system that allows the temporary housing of those affected is proposed. To complete the design, the selection of materials is necessary through a methodology based on the guidelines LCA (Life Cycle Assessment) on the life cycle of materials with categories indicating their importance depending on the building component such as foundation, structure, walls and cover in relation to the type of building that although this research exercise is applied to the design of temporary shelters can be replicated in the design of other types of buildings. The selection of materials is presented as the basis for a later stage of environmental simulations where different configurations with better performance materials are proposed in order to also evaluate the thermal performance and tend to minimize the environmental impact.
Keywords: Analysis of variables; Temporary shelter; Life cycle; Sustainable design; construction system; selection of materials